2006
DOI: 10.4028/www.scientific.net/msf.514-516.98
|View full text |Cite
|
Sign up to set email alerts
|

Push-Pull Tricyanovinyl-Substituted Thienylpyrroles: Synthesis, Solvatochromic and Electrochemical Properties

Abstract: New tricyanovinyl-derivatives 1 of 1-(alkyl)aryl-2-(2'-thienyl)pyrroles 2 have been synthesized and characterized. Compounds 1 display dramatic reductions in both their optical and electrochemical band gaps in comparison to thienylpyrroles 2. The solvatochomic behavior of tricyanovinyl-derivatives 1 was investigated in a variety of solvents. In agreement with the solvatochromic and the electrochemical studies for pushpull derivatives I the new compounds prepared, can find application for manufacturing new mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that donor-acceptor substituted pyrroles exhibit a positive solvatochromism. [8][9][10][11][12][19][20] In this case a moderate to large positive solvatochromism (Δν max = 488-981 cm -1 ) was observed moving from diethyl ether to DMSO solutions for derivatives 1a-e. The UV-visible spectra of 1b in ethyl ether and in DMSO are given in figure 5.…”
Section: Linear and Nonlinear Optical Properties Of The Chromophoresmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have demonstrated that donor-acceptor substituted pyrroles exhibit a positive solvatochromism. [8][9][10][11][12][19][20] In this case a moderate to large positive solvatochromism (Δν max = 488-981 cm -1 ) was observed moving from diethyl ether to DMSO solutions for derivatives 1a-e. The UV-visible spectra of 1b in ethyl ether and in DMSO are given in figure 5.…”
Section: Linear and Nonlinear Optical Properties Of The Chromophoresmentioning
confidence: 92%
“…spectra is observed when stronger acceptor groups are linked to the heterocyclic system. [8][9][10][11][12][19][20] As a result the substitution of a formyl group for a 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile moiety leads to a red shift of 170 nm from 348 nm (1a) to 510 nm (1e). Within the series 1a-e the CT bands moves to lower energy as the electron accepting ability of the acceptor moiety increases, in the order CHO < dicyanovinyl < rhodanine < thiobarbituric acid < 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile (Fig.…”
Section: Linear and Nonlinear Optical Properties Of The Chromophoresmentioning
confidence: 97%
See 1 more Smart Citation